Does nitrate reductase play a key role in photoinduction of carotenoid synthesis in Neurospora crassa? - T. A. Belozerskaya; S S. Burikhanov; E. K. Chernyshova; M. S. Kritsky; N. P. Lvov (Fungal Genetics Reports, 1982)
Does nitrate reductase play a key role in photoinduction of caroteniod synthesis in Neurospora crassa?